2007
DOI: 10.1038/labinvest.3700657
|View full text |Cite
|
Sign up to set email alerts
|

CD151 dynamics in carcinoma–stroma interaction: integrin expression, adhesion strength and proteolytic activity

Abstract: A member of tetraspanin CD151 is a scaffold protein of laminin-binding integrins and it plays an important role in stable interaction between cells and basement membrane. Although the upregulation of CD151 in tumor cells is thought to accelerate tumor invasion and metastasis, detailed pathological investigation on CD151 and its association with integrins has not been well documented, yet. In the present study, we showed that the expression levels of CD151 and its associated integrin subunits in epidermal carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 41 publications
2
52
1
Order By: Relevance
“…Further support for this view comes from another recent study in which CD151 was silenced in H5SC carcinoma cells, resulting in redistribution of cortical actin and enhanced stress fibers (Hasegawa et al, 2007). Lastly, our results contrast with a recently published study that demonstrated decreased gap filling in vitro by MCF-10A cells treated with a CD151 siRNA (Yang et al, 2008).…”
Section: Cd151 Regulates Rhoa Activation E-cadherin Junctional Stabicontrasting
confidence: 57%
See 1 more Smart Citation
“…Further support for this view comes from another recent study in which CD151 was silenced in H5SC carcinoma cells, resulting in redistribution of cortical actin and enhanced stress fibers (Hasegawa et al, 2007). Lastly, our results contrast with a recently published study that demonstrated decreased gap filling in vitro by MCF-10A cells treated with a CD151 siRNA (Yang et al, 2008).…”
Section: Cd151 Regulates Rhoa Activation E-cadherin Junctional Stabicontrasting
confidence: 57%
“…For example, whereas tetraspanins CD9 and CD82 are potential metastasis suppressors (Boucheix et al, 2001;Lazo, 2007;Liu and Zhang, 2006;Tonoli and Barrett, 2005), tetraspanin CD151 has been linked to enhanced metastasis of colon, prostate and lung cancer (Ang et al, 2004;Hashida et al, 2003;Tokuhara et al, 2001). The mechanisms whereby tetraspanins might regulate metastasis can be grouped into several classes, including regulation of (i) pericellular matrix proteolysis (Gesierich et al, 2006;Hasegawa et al, 2007;Hong et al, 2006;Hong et al, 2005;Huang et al, 2007;Saito et al, 2006;Sugiura and Berditchevski, 1999), (ii) integrin cell-surface expression and trafficking (Berditchevski and Odintsova, 2007;Liu et al, 2007;Winterwood et al, 2006), (iii) integrin-dependent migration, invasion and signaling (Berditchevski, 2001;Hemler, 2005), (iv) integrin crosstalk with growth factor receptors (Sridhar and Miranti, 2006) and (v) pathological angiogenesis (Gesierich et al, 2006;Takeda et al, 2007). Most of these proposed tetraspanin functions center around regulation of cell-extracellular matrix interactions and downstream signaling events.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In contrast, tumor-stromal fibroblasts not forming fibrotic foci commonly admix with many tumor cells that show stromal invasion. This difference p53 expression in tumor-stromal fibroblasts strongly suggests that the tumor cell-stromal cell interaction occurs more frequently in the outer area of a fibrotic focus than in the inner area of a fibrotic focus within IDCs, 10,11 probably resulting in the higher Allred scores for p53 in tumor-stromal fibroblasts not forming fibrotic foci. However, the Allred scores for p53 in tumor-stromal fibroblasts forming fibrotic foci were significantly associated with those for p53 in tumor-stromal fibroblasts not forming fibrotic foci.…”
Section: Discussionmentioning
confidence: 97%
“…6,7 Because it has recently been reported that the gene expression profile and protein expression profile of the tumor stroma have a very important function in tumor progression in carcinoma 8,9 and that the interactions between tumor cells and stromal cells also are very important in tumor progression in carcinomas, 10,11 these findings strongly suggest that the tumor stroma has a significant function in tumor progression in IDCs. Mutations of the p53 tumor suppressor gene have been described in the stromal fibroblasts of breast and prostate carcinomas in humans and experimental animals, [12][13][14] and p53 mutations in breast cancer stromal cells have been reported to be closely associated with nodal metastasis.…”
mentioning
confidence: 85%
“…MMP-7 activity was also confirmed around the human lung adenocarcinoma cell nests, the sites of CD151 and MMP-7 colocalization. 61,62 However, reported by Shiomi et al a remarkably strong interaction of CD151 with pro-MMP-7, observed even in stringent conditions, has not been so far confirmed by other groups. Moreover, presented recovery of interaction was supposed to involve the large extracellular loop (EC2) of CD151.…”
Section: Interactions With Mmpsmentioning
confidence: 80%